2013
DOI: 10.1002/bjs.8996
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a fast-track programme for patients undergoing liver resection

Abstract: Background: Recent developments in perioperative pathophysiology and care have documented evidence-based, multimodal rehabilitation (fast-track) to hasten recovery and to decrease morbidity and hospital stay for several major surgical procedures. The aim of this study was to investigate the effect of introducing fast-track principles for perioperative care in unselected patients undergoing open or laparoscopic liver resection.Methods: This was a prospective study involving the first 100 consecutive patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 29 publications
8
67
0
3
Order By: Relevance
“…Finally, hospital LOS in other studies was longer [41] . The ERAS programme could explain this faster recovery [21,42] .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, hospital LOS in other studies was longer [41] . The ERAS programme could explain this faster recovery [21,42] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the introduction of standardized perioperative care pathways promoting best practices has accelerated recovery following other types of surgical procedure, data evaluating the implementation of similar best practices following liver surgery are lacking 4,6,11 . The few studies assessing ERAS protocols following liver surgery have demonstrated improved perioperative outcomes, but these reports are limited in their generalizability, small sample size and lack of adequate controls for comparison 5,12 . Given this, an evidence-based and standardized perioperative care pathway was designed and implemented prospectively among patients undergoing open liver surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Initially introduced in the mid-1990s, the enhanced recovery after surgery (ERAS) programme represents one such paradigm designed to reduce the surgical stress response and accelerate postoperative recovery 3 . Promoting the adoption of evidence-based best practices, ERAS programmes focus on patient education, goal-directed fluid management, decreased use of unnecessary nasogastric tubes and peritoneal drains, minimal use of opioid analgesia, as well as early mobilization and resumption of oral intake 1,3,5,6 . Widely adopted for colorectal and orthopaedic surgery, these programmes have been effective in reducing length of stay and morbidity while improving the value of care and patient satisfaction after surgery 1,2,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Die durch die laparoskopische Operation bereits deutlich verkürzte Erholungszeit [8,17,21] kann durch adäquate Anäs-thesieverfahren mit Periduralkatheter, frühzeitige Mobilisation und Ernährung sowie die frühzeitige Entfernung aller invasiven Zugänge noch weiter abgesenkt werden [22,26] Weitere Entwicklungen der minimalinvasiven Leberchirurgie gehen mit der Entwicklung von Robotersystemen einher [30]. Hier ist die Bedeutung bisher nicht absehbar.…”
Section: Postoperativer Verlauf Und Fasttrackunclassified